Cover Image. (6th February 2020) - Grothe, Torsten; Wandrey, Franziska; Schuerch, Cornelia
Abstract : The cover image is based on the Short Communication* Short communication: Clinical evaluation of pea sprout extract in the treatment of hair loss by Torsten Grothe ** et al., https://doi.org/10.1002/ptr.6528 .***